2019
DOI: 10.1128/msphere.00018-19
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Pathogenic, Genomic, and Chemical Traits of Aspergillus fischeri , a Close Relative of the Major Human Fungal Pathogen Aspergillus fumigatus

Abstract: Aspergillus fumigatus is the primary cause of aspergillosis, a devastating ensemble of diseases associated with severe morbidity and mortality worldwide. A. fischeri is a close relative of A. fumigatus but is not generally observed to cause human disease. To gain insights into the underlying causes of this remarkable difference in pathogenicity, we compared two representative strains (one from each species) for a range of pathogenesis-relevant biological and chemical characteristics. We found that disease prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 94 publications
(131 reference statements)
6
89
1
Order By: Relevance
“…Support for the role of genetic differences in contributing to the observed spectrum of pathogenicity is provided by the numerous traits, and their underlying genes and pathways, that are required for pathogenicity in A. fumigatus [2,19,20,37] and have been found to exhibit substantial genetic and phenotypic diversity among section Fumigati species. These traits include thermotolerance, the ability to respond to multiple environmental stresses, including antifungal drugs, and the capacity to biosynthesize a range of structurally diverse secondary metabolites [14,30,38,39].…”
Section: The Observed Spectrum Of Pathogenicity Cannot Be Explained Bmentioning
confidence: 99%
See 3 more Smart Citations
“…Support for the role of genetic differences in contributing to the observed spectrum of pathogenicity is provided by the numerous traits, and their underlying genes and pathways, that are required for pathogenicity in A. fumigatus [2,19,20,37] and have been found to exhibit substantial genetic and phenotypic diversity among section Fumigati species. These traits include thermotolerance, the ability to respond to multiple environmental stresses, including antifungal drugs, and the capacity to biosynthesize a range of structurally diverse secondary metabolites [14,30,38,39].…”
Section: The Observed Spectrum Of Pathogenicity Cannot Be Explained Bmentioning
confidence: 99%
“…For the trait reconstruction inference, Biosafety Level (BSL) 2 organisms were considered pathogenic and BSL1 organisms or organisms that so far lack BSL labelling were considered non-pathogenic; these transitions to a pathogenic lifestyle (i.e., from BSL1 to BSL2) are labelled by red bars on the figure. Note that clinical isolates from humans or other mammals from a few additional species in the section have been identified [10,28]; this handful includes relatively newly described species that some authors consider to have pathogenic potential (e.g., Aspergillus novofumigatus [29]) as well as organisms thought to be on the non-pathogenic end of the spectrum (e.g., A. fischeri [30,31]). The phylogeny of the section was redrawn from Hubka et al [16].…”
Section: Two Models For the Evolution Of Pathogenicity In Aspergillusmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in sharp contrast to primary metabolic genes, which are 7.5%–15.4% species-specific (7). Comparisons between more closely related species using A. fumigatus and Neosartorya fischeri or Aspergillus novofumigatus , which all belong to Aspergillus section Fumigati revealed that 30.3% or 70.5% of A. fumigatus SM genes were shared, respectively (8,9). Comprehensive genomic studies in Aspergillus sections Nigri and Flavi also showed overlaps of SM genes at specific rates.…”
Section: Introductionmentioning
confidence: 99%